Accounting emergy-based sustainability of crops production in India and Pakistan over first decade of the 21st century. (10th January 2019) - Ali, Mustafa; Marvuglia, Antonino; Geng, Yong; Robins, Dawn; Pan, Hengyu; Song, Xiaoqian; Yu, Zhongjue; Sun, Huaping
Abstract: Agriculture is one of the main assets of Pakistani and Indian economies, employing in both countries about 50% of the total labour force. Thus, improving agricultural sustainability in the Indo-Pak region has important implications for the local population as well as the rest of the world that relies on food imports from these countries. This article investigates the drivers and consequences of changes in crop production sustainability in India and Pakistan from an emergy-based perspective, from 2001 to 2011. However, due to the numerous crops cultivated in these regions, a detailed calculation of unit emergy values (UEVs) for each crop was not possible, therefore the paper presents a balance at country level (based on literature data for the crops' UEVs), rather than a canonical emergy accounting. The emergy perspective was chosen to holistically evaluate and compare the environmental pressures caused by crop production in both countries. Emergy-based indicators were calculated based on the real time series of input renewable and non-renewable sources. The major findings of the work revealed that purchased renewable inputs, such as irrigating water, and purchased non-renewable inputs, such as agricultural labor, are the largest contributors among the total inputs in both countries. Labor accounted for 46.79% and 60.59% of total emergy input for crop production in India and Pakistan respectively. Overall, the production efficiency in India was greater than that in Pakistan. Emergy of crop production in Pakistan witnessed an increase of only 23%, whereas India saw an increase of 42% during the study period. Despite the lack of data on each specific agricultural process, this trend is an evidence of the fact that, if on one side the agricultural activities in the two countries were intensified to supply an increasing population, on the other side, although India performed better than Pakistan, the sustainability of the agricultural practices (from a nature-oriented perspective as assessed with emergy analysis) in both countries did not improve. . Trends of carrying capacity indicated that intensive means of agricultural production are threatening natural resources in both countries. This study empirically demonstrates the need to conserve natural resources, especially water, which have been rapidly declining in these two countries. Since both countries share these resources, this study represents an evidence for the need to cooperate for transboundary natural resource management.